Reducing the psychosocial impact of aphasia on mood and quality of life in people with aphasia and the impact of caregiving in family members through the Aphasia Action Success Knowledge (Aphasia ASK) program: study protocol for a randomized controlled trial. Issue 1 (December 2016) - Worrall, Linda; Ryan, Brooke; Hudson, Kyla; Kneebone, Ian; Simmons-Mackie, Nina; Khan, Asaduzzaman; Hoffmann, Tammy; Power, Emma; Togher, Leanne; Rose, Miranda
Abstract Background People with aphasia and their family members are at high risk of experiencing post stroke depression. The impact of early interventions on mood and quality of life for people with aphasia is unknown. Methods/design This study will determine whether an early intervention for both the person with aphasia after stroke and their family members leads to better mood and quality of life outcomes for people with aphasia, and less caregiver burden and better mental health for their family members. This is a multicenter, cluster-randomized controlled trial. Clusters, which are represented by Health Service Districts, will be randomized to the experimental intervention (Aphasia Action Success Knowledge Program) or an attention control (Secondary Stroke Prevention Information Program). People with aphasia and their family members will be blinded to the study design and treatment allocation (that is, will not know there are two arms to the study). Both arms of the study will receive usual care in addition to either the experimental or the attention control intervention. A total of 344 people with aphasia and their family members will be recruited. Considering a cluster size of 20, the required sample size can be achieved from 18 clusters. However, 20 clusters will be recruited to account for the potential of cluster attrition during the study. Primary outcome measures will be mood and quality of life of people with aphasia at 12 months post stroke. Secondary measures will be family member outcomes assessing the impact of caregiving and mental health, and self-reported stroke risk-related behaviors of people with aphasia. Discussion This is the first known program tailored for people with aphasia and their family members that aims to prevent depression in people with aphasia by providing intervention early after the stroke. Trial registration This trial is registered in the Australian New Zealand Clinical Trials Registry (ANZCTR) asACTRN12614000979651 . Date registered: 11 September 2014.